If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2x = 3(x + 4) + -2 Reorder the terms: 10 + -2x = 3(4 + x) + -2 10 + -2x = (4 * 3 + x * 3) + -2 10 + -2x = (12 + 3x) + -2 Reorder the terms: 10 + -2x = 12 + -2 + 3x Combine like terms: 12 + -2 = 10 10 + -2x = 10 + 3x Add '-10' to each side of the equation. 10 + -10 + -2x = 10 + -10 + 3x Combine like terms: 10 + -10 = 0 0 + -2x = 10 + -10 + 3x -2x = 10 + -10 + 3x Combine like terms: 10 + -10 = 0 -2x = 0 + 3x -2x = 3x Solving -2x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2x + -3x = 3x + -3x Combine like terms: -2x + -3x = -5x -5x = 3x + -3x Combine like terms: 3x + -3x = 0 -5x = 0 Divide each side by '-5'. x = 0 Simplifying x = 0
| 10h=-.1 | | 9=2j+1 | | 9=1+2b | | 3x+2(x+2)=5x+4 | | -2.5s=25 | | 2x+2+7x=-6x-2x | | .4x-8+.5x=19 | | 2(x+1)=3(x+4) | | 4+2i=4 | | 12y=1x+b | | -8g=.48 | | 0.6r=.0005 | | -7y=-6.3 | | 2(x+1)=3(x+4)+10 | | 0.6=r+.0005 | | (3x^2-2x^2+2x-5)*x+1= | | x+(-28)=53 | | .3k=-12 | | 14=6-4y | | 3(10x+4)=8(3x+6) | | z^2=z-12 | | 5r=-.15 | | 3x+2(x+2)=5-4x+2 | | (2x-5)/6-(3x-2)/3=(2x-5)/2 | | .0005=0.6r | | 3x+14=7x+2 | | -6x+5=77+2x | | 20y+3=7 | | 5x-7=-7x+29 | | .0005=0.6 | | -2x-10=-7-5x | | 0.75+2(x-0.5)=2p |